Metabolic profiling comparison of isovitexin in normal and kidney stone model rats by ultra‐high‐performance liquid chromatography coupled to quadrupole time‐of‐flight mass spectrometry. Issue 12 (5th May 2020) - Meng, Caifeng; Liu, Ruina; Wang, Wei; Guo, Wei; Ma, Hongyun; Xie, Shuang; Liu, Yimeng; Wang, Chunying
Abstract: Isovitexin, a bioactive flavonoid constituent isolated from Desmodii Styracifolii, is considered an adjuvant for antiurolithiasis diseases. In this study, an ultra‐high‐performance liquid chromatography coupled with hybrid triple quadruple time‐of‐flight mass spectrometry method was developed to characterize and compare the metabolic profiling of isovitexin experimented on normal and kidney stone model rats. The comparative research indicated that 28 metabolites (18 phase I and 10 phase II) in normal rats and 33 metabolites (20 phase I and 13 phase II) in kidney stone model rats were initially identified. The results of relative quantitative determination reflected that the contents of metabolites produced by deglycosylation, reduction, and isomerization in kidney stone model rats were greater than those in healthy rats. Instead, the levels of oxidative and dehydrogenated metabolites in normal groups were higher than those in kidney stone model groups. The results of this study are valuable and important for understanding the metabolic process of isovitexin in clinical application, and especially the metabolism study in kidney stone model rats could provide a beneficial reference for the further search of effective substances associated with the treatment of kidney stones.